Influencers and targets on social media: Investigating the impact of network homogeneity and group identification on online influence - Sanna Malinen; Aki Koivula (The University of Illinois at Chicago University Library, 2022)
This study identifies social media users who aim to influence others and those who have experienced influencing behavior targeted at them. It investigates how influential users and targets of influence differ with respect to their demographic backgrounds and how the perceived group identification, network homogeneity, and size of the social network affect online influence. The data was based on a large-scale survey of Finnish people (N=2,761). We find that young and highly educated men were more likely to be targets of influence, but the demographic differences were less obvious with regard to influencing behavior. Moreover, group identification was a significant factor underpinning online influence for both influencing behavior and target experiences. The network homogeneity and the size of the network increased the likelihood of influencing behavior. Our main contribution is to shed light on people who are targets of online influencing on social media. By comparing influential users and their targets, this study extends the previous research, which has mostly focused on detecting influential people.